STRATEGI KONSELING INDIVIDUAL DAN KELOMPOK BERBASIS NILAI ISLAM DALAM PENANGANAN SANTRI KORBAN BULLYING DI PESANTREN - Nadila Farahita; Dina Hajja Ristianti; Beni Azwar; Sumarto (STKIP Subang, 2026)
Bullying is a form of social violence that frequently occurs in educational environments, including Islamic boarding schools (pesantren), and has negative impacts on students’ psychological, social, spiritual, and academic conditions. Previous studies generally focused only on the causes of bullying or discussed counseling services separately, so there are still limited studies integrating individual and group counseling based on Islamic values in handling students who are victims of bullying in pesantren. This study aims to examine the impacts of bullying on students and the strategies of individual and group counseling in addressing victims of bullying in Islamic boarding schools. This research employed a qualitative approach using a library research method. Data were collected through documentation studies from books, scientific journals, and relevant research articles, then analyzed using content analysis techniques. The findings revealed that victims of bullying experience anxiety, trauma, low self-esteem, and difficulties in social interaction and learning activities. Individual counseling helps students recover emotionally and rebuild self-confidence, while group counseling provides social support and improves social interaction skills. This study contributes to the development of Islamic guidance and counseling studies through the integration of individual and group counseling services in handling students who are victims of bullying in Islamic boarding schools.